Determination of FICI of Ethanolic Extract of Aloe Vera Skin Leaves (Aloe vera (L.) Burm.f.) and Gentamicin Sulphate againts Staphylococcus aureus - Rifani Amalia; Rafika Sari; Robiyanto Robiyanto (Faculty of Pharmacy, Universitas Gadjah Mada, 2017)
The main therapy of wounds infection using antibiotic such as gentamicin sulfate can be applied topically. Increasing incidence of antibiotic resistance forces new strategy to combine plant extract and antibiotic. These two combinations are expected to reduce the incidence of microbial resistance. Ethanolic extract of Aloe vera skin leaves contain anthraquinone that has antimicrobial activity. The aim of this study was to determine the effect and Fractional Inhibitory Concentration Index (FICI) from combination of ethanolic extract of Aloe vera skin leaves and gentamicin sulphate which can inhibit the growth of Staphylococcus aureus. Minimum Inhibitory Concentration (MIC) determination was used Kirby-Bauer disc diffusion method. The concentration of extract solution used were 1,25; 2,5; 5; 10 mg/mL while the solution concentration of gentamicin sulfate used were 2,5; 5; 15; 25 µg/mL. Solution DMSO was used as negative control. Combination solution was made with volume ratio 1:1 from MIC of extract and gentamicin shulphate. The result showed that the MIC of the of ethanolic extract of Aloe vera skin leaves was about 2.5 mg/mL and MIC gentamicin sulphate was about 5 µg/mL. Combination of ethanolic extract of Aloe vera skin leaves and gentamicin sulfate can inhibit the growth of Staphylococcus aureus with zone of inhibition 7,63 mm. FICI of combination was 2 and its antibacterial activity was indifferent compared to single extract and single gentamicin sulphate.